Methods of snow avalanche nourishment assessment (on the example of three Tian Shan glaciers) - A. S. Turchaninova; A. V. Lazarev; E. S. Marchenko; Yu. G. Seliverstov; S. A. Sokratov; D. A. Petrakov; M. Barandun; R. Kenzhebaev; T. Saks (Лëд и снег, 2019)
The contribution of snow avalanches to the seasonal snow accumulation on a glacier is among the least studied components of the glacier’s mass balance. The methods for the numerical assessment of avalanche accumulation are still under development, which is related to poor avalanche data availability and difficulties in obtaining such data on most of mountain glaciers. We propose a possible methodology for the numerical assessment of snow avalanche contribution to snow accumulation at mountain glaciers based on DEM and weather data analysis using GIS and numerical modeling of snow avalanches. The developed methodology consists of the following steps: terrain analysis; weather data analysis; snow avalanche volume assessment during an analyzed balance year; numerical simulation of snow avalanches using RAMMS; evaluation of snow avalanches contribution into a glacier accumulation. The proposed methodology was tested on three glaciers located in the Inner Tien Shan: Batysh Sook, № 354 and Karabatkak during the 2015/16 balance year. To evaluate snow avalanche contribution to the seasonal accumulation, we reconstructed avalanche release zones that were most probably active during the 2015/16 balance year and corresponding snow fracture height in each of these zones. The numerical simulations of most probable released snow avalanches during the winter period 2015/16 using avalanche dynamics software RAMMS were performed and compared with the field observations and UAV orthophoto image from July 2016. The outlines of avalanches deposits were realistically reproduced by RAMMS according to the results of field observation. The estimated share of snow avalanche contribution to the accumulation on the research glaciers during the 2015/16 balance year turned out to be: Batysh Sook – 7,4±2,5%; № 354 – 2,2±0,7%; Karabatkak – 10,8±3,6% of the total accumulation. The next step would be to test the proposed methodology based on the data and regional dependences from the Inner Tien Shan in other mountainous regions. This methodology is applicable in the regions where DEMs, regular meteorological observations as well as data on the regional avalanche formation factors are available.